Surveying the relationships between the goal orientations of the students sporting as team sport and individualistically and the level of their basic psychologic needs at the school of physical education and sports - Tekin, Murat; Yildiz, Mustafa; Sahan, Hasan; Devecioglu, Sebahattin; Gullu, Mehmet; Ulucan, Buket (Elsevier Science Bv, 2012)
The aim of this study is surveying the relationships between the goal orientations of the students sporting as team sport and individualistically and the level of their basic psychologic needs at the school of physical education and sports. 126 male and 83 femal in total 209 students sporting actively at the schools of Physical Education and Sports of Gazi University, Selcuk University, Karamanoglu Mehmetbey University and Ataturk University attended the survey (average of age is 22.3971 +/- 1.75 years). Firstly, the present data concerning the aim of the study has been given systematically by reviewing the literature. Thus, a theoretical framework has been formed. Secondly, Scale of Task and Ego Orientation of Sports developed by Duda (1989) and adapted to Turkish athletes by Toros (2001) and Basic Psychological Needs Scale Decive Ryan (2000) adapted to Turkish by Kesici, Ure et al. (2003) have been applied to the students to achieve the objectives of the research. In the analysis and commenting the data; by using the pearson product moment correlation statistical technique, P<0,05 significance has been taken. SPSS (Statistical package for social sciences) has been used in the evaluation of the data and finding the estimated values. In the result of this research, a significance relationship was found between the task and ego orientations and self determination and competence and level of relationships of the students sporting as team sport. According to these results, the success level of the students sporting as team sport about their competence and self determination decides that they contribute positively the evaluations regarding how good the individual's daytime will be. The findings in this study were parallel with the current study. There has been no significant relationship between the self determination and competence levels of the students sporting as individualistically, a significant relationship has been found between the relationship levels. These results reveal that ego-oriented sportsmen focus on external criteria to indicate achievement and believe the importance of opportunities and social comparisons as the achievement criteria and the conclusion that these behaviours are more important for ego-oriented sportsmen than perceived abilities, intense work and effort.
4th World Conference on Educational Sciences (WCES) -- FEB 02-05, 2012 -- Univ Barcelona, Barcelona, SPAIN
Keywords: Physical Education; Team Sport; Sports; Individual Sports; Goal Orientations; Psychologic Needs